Northern hemisphere climate control on the environmental dynamics in the glacial Black Sea "Lake". (1st March 2016) - Wegwerth, Antje; Kaiser, Jérôme; Dellwig, Olaf; Shumilovskikh, Lyudmila S.; Nowaczyk, Norbert R.; Arz, Helge W.
Abstract: The Marine Isotope Stage (MIS) 3 stands out due to its abrupt changes from cold and dry stadials to warm and humid interstadials, the so-called Dansgaard-Oeschger cycles that also affected temperature and rainfall in the Black Sea region. This study is based on a gravity core from the southeastern (SE) Black Sea that covers the last glacial lake stage from 64 to 20 ka BP. By using the composition of major and trace elements in the sediments, terrestrial plant-derived n -alkane flux, and Sr/Ca from benthic ostracods, we reconstruct the variability of riverine and aeolian input, salinity, and productivity in the SE Black Sea region in response to the Northern Hemisphere climate oscillations. During colder and drier stadials, the aeolian input increased relative to the riverine discharge, potentially due to southward shifted and/or stronger westerly winds and due to changes in the vegetation cover. An evaporation exceeding freshwater supply by rainfall and rivers possibly caused higher salinity and a lower lake level. The environmental status during MIS 4 and 2 is very much comparable with the stadial conditions during MIS 3. During warmer and more humid interstadials, lower salinity and presumably positive lake level changes most likely resulted from increased precipitation and river discharge. This likely increased primary productivity through an augmented nutrient supply. Lowest average salinities are suggested for the middle part of MIS 3 in response to enhanced meltwater from the disintegrating Fennoscandian Ice Sheet and/or by generally more humid conditions. Highlights: Black Sea record between 64 and 20 ka BP is presented. Main parameters are K/Ti, Ti/Al, Zr/Al, n -C27 - n -C31 n -alkanes, and Sr/Caostracods . Higher aeolian input and salinity and low productivity during stadials. Higher riverine input and productivity and low salinity during interstadials. Long-term pattern shows freshening during first part of MIS 3.